Avaliação de desempenho da cadeia de suprimentos do hidrogênio verde baseada em simulação de sistemas a eventos discretos - Silva, William Neves da (2024)
The relentless search for alternative and renewable energy sources has been a recurring theme in global debates, mainly due to the need to meet the growing energy demand of the population and mitigate the environmental impacts caused by non-renewable fuels, which exacerbate the emission of carbon dioxide (CO2) into the atmosphere, contributing to the greenhouse effect and global warming. In this scenario, solar, wind and biomass energy are emerging as protagonists in this search for sustainable solutions. A promising option then emerges, Green Hydrogen (G2H), produced through the electrolysis of water, which presents itself as a viable energy vector to drive the energy transition. However, despite its potential, significant investments in technology are still needed to overcome challenges such as the complex storage of G2H and the development of adequate infrastructure for its transportation. As a methodological proposal, a series of steps are used, divided into nine interrelated steps, which guide the development of the simulation. In this context, this Dissertation project aims to evaluate the G2H supply chain, employing discrete event system simulations, using bibliometric analysis to identify and highlight the main obstacles in this area. The development of specific simulation models will allow a detailed analysis of several scenarios, using values extracted from the literature such as production, cost and process parameters. From this, valuable insights will be provided to managers, assisting in decision-making throughout the entire green hydrogen production chain.